WWSSF - a worldwide study on radioisotopic renal split function: reproducibility of renal split function assessment in children - Geist, Barbara Katharina; Dobrozemsky, Georg; Samal, Martin; Schaffarich, Michael P; Sinzinger, Helmut; Staudenherz, Anton (Nuclear medicine communications, 2015)
PURPOSE: The split or differential renal function is the most widely accepted quantitative parameter derived from radionuclide renography. To examine the intercenter variance of this parameter, we designed a worldwide round robin test. METHODS: Five selected dynamic renal studies have been distributed all over the world by e-mail. Three of these studies are anonymized patient data acquired using the EANM standardized protocol and two studies are phantom studies. In a simple form, individual participants were asked to measure renal split function as well as to provide additional information such as data analysis software, positioning of background region of interest, or the method of calculation. RESULTS: We received the evaluation forms from 34 centers located in 21 countries. The analysis of the round robin test yielded an overall z-score of 0.3 (a z-score below 1 reflecting a good result). However, the z-scores from several centers were unacceptably high, with values greater than 3. In particular, the studies with impaired renal function showed a wide variance. CONCLUSION: A wide variance in the split renal function was found in patients with impaired kidney function. This study indicates the ultimate importance of quality control and standardization of the measurement of the split renal function. It is especially important with respect to the commonly accepted threshold for significant change in split renal function by 10%.
Keywords: radioisotopová scintigrafie; vyšetření funkce ledvin; ledviny; reprodukovatelnost výsledků; Kidney; lidé; Kidney Function Tests; Radionuclide Imaging; Reproducibility of Results; internacionalita; dítě; radionuklidy; Child; Humans; Radioisotopes; Internationality